The Problems of Islamic Religious Education Teacher for Curriculum Development in Transmigration Area - Shalihin, Rahmat Ryadhush; Widodo, Hendro (Nadwa: Jurnal Pendidikan Islam, 2019)
This paper aims to analyze the problematics of teacherÂ  to develop curriculum Islamic Religious Education . This research used qualitative methods and data were gathered from literature reviews, observations, and in-depth interviews from teacher and student. The data analyzed with reduction, presentation, and conclusion. The results of this research revealed that The problems of Islamic education teachers in transmigration areas can be summarized into five things. They are first, they have to deal with active time management Secondary learning, management documents, such as students daily paper sheets, Learning Perfoming Plan / RPP, and other extra tasks from school and headmaster to the teacher for some training. Third, the lack of teaching materials causes. Fourth, the problem of conditional and competency teachers. Fifth, they have passive studentsKeywords: Islamic education; transmigration era, problem teacher; curriculum developmentAbstrakMakalah ini bertujuan untuk menganalisis problematika guru dalam mengembangkan kurikulum Pendidikan Agama Islam. Penelitian ini menggunakan metode kualitatif dan data dikumpulkan dari tinjauan literatur, observasi, dan wawancara mendalam dari guru dan siswa. Data dianalisis dengan reduksi, presentasi, dan kesimpulan. Hasil penelitian ini mengungkapkan bahwa masalah guru pendidikan Islam di daerah transmigrasi dapat diringkas menjadi lima hal. Mereka adalah yang pertama, mereka harus berurusan dengan manajemen waktu aktif Pembelajaran sekunder, dokumen manajemen, seperti kertas harian siswa, Rencana Pembelajaran Perfoming / RPP, dan tugas tambahan lainnya dari sekolah dan kepala sekolah kepada guru untuk beberapa pelatihan. Ketiga, kurangnya bahan ajar menyebabkan. Keempat, masalah guru bersyarat dan kompetensi. Kelima, mereka memiliki siswa pasifKata kunci: pendidikan Islam; era transmigrasi, guru bermasalah; pengembangan kurikulum